Robust digital watermark method based on PDF417 two-dimension code - Cui-ling JIANG; Shuai HUANG; An-wen WU; Wen-xin YU; Zhou-mao KANG; Yong-qiang LI (网络与信息安全学报)
A digital watermark method based on the bar-block-margin characteristics of PDF417 two-dimension code was presented.The proposed method prejudges the watermark information to choose the suitable embedding positions.According to the watermark,the information of the original PDF417 image was modified for embedding and extracting.The experimental results showed that,in comparison with the other methods in the spatial domain,the proposed method has a higher capacity and better watermarked image quality,as well as better robustness against JPEG compression,Gaussian noise and printing and scanning.